Assessing the quality of routine HIV testing data in the community setting 'COBATEST Network'. (September 2019) - Reyes-Urueña, J; Fernàndez-Lopez, L; Montoliu, A; Conway, A; Tavoschi, L; Klavs, I; Cosmaro, L; Eibl, I; Dominković, Z; Pichon, F; Casabona, J; ,
The COBATEST Network of Community-Based Voluntary Counselling and STI/HIV Testing (CBVCT) services was created to standardise monitoring and evaluation of CBVCT services across Europe. This study aims to assess the quality of data collected in the network from 2015 to 2016. A survey was completed by 34 COBATEST Network members and an evaluation was performed of data quality based on three dimensions: transcription validity, completeness and consistency. The weakest area that we identified was data management processes. Only 8.8% of services had a written procedure to address data quality errors, 29.4% had procedures in place to resolve discrepancies and 35.3% performed quality control. We found that 41.2% of services utilised the COBATEST data, 11.8% made decisions based on the COBATEST data and 61.8% analysed their data in an independent manner for internal purposes. We conclude that while services have reliable data to support planning and management of services, improvements to quality procedures would ensure data are translated into evidence. This evidence would support further expansion of CBVCT services in the EU/EEA, including the integration of CBVCT-generated data into national surveillance systems.